Changes in fatty acid composition and conjugated linoleic acid contents of milk and dairy products caused by pure cultures as well as during microwave heat treatment - Salamon, Rozália Veronika; Lóki, Katalin; Salamon, Szidónia; Albert, Beáta; Mándoki, Zsolt; Csapóné Kiss, Zsuzsanna; Sára, Péter; Borosné Győri, Anikó; Győri, Zoltán; Csapó, János (Acta Agraria Kaposváriensis, 2007)
In the first part of this research we have investigated the effect of various pure cultures (Lactobacillus lactis subsp. lactis, Lactobacillus lactis subsp. cremoris, Streptococcus salivarius subsp. thermophilus, Lactobacillus delbrueckii subsp. bulgaricus, Lactobacillus lactis subsp. lactis biovar, Lactobacillus diacetilactis, Lactobacillus acidophilus, Bifidobacterium lactis) on fatty acid composition of soured dairy products (Sana, yoghurt) manufactured using different technologies, with special regard to conjugated linoleic acid (CLA). It was established that the cultures we used and which are also commonly used in the dairy industry, had only a slight effect on fatty acid composition of milk. Although minimal differences were found in case of the individual fatty acids, however, due to the small differences it can be established that the cultures have no influence on nutritional value of milk fat. In the second part of our experiments we have determined fatty acid composition of cow's milk with fat contents of 3.6%, Dalia cheese with fat contents of 44%, butter with fat contents of 80% and margarine with fat contents of 24% after a heat treatment performed on cooking plate and microwave treatment, respectively of different durations. The biggest difference was obtained for oleic acid and elaidic acid since with the exception of the margarine in each case proportion of the cis-configurated oleic acid decreased while that of the trans-configurated elaidic acid increased. For all of the other fatty acids in the foodstuffs examined no such differences were obtained regarding change in fatty acid composition, which differences could influence healthy nutrition to considerable extent, therefore we can take it as a fact that neither heat treatment performed on a traditional cooking plate nor microwave treatment affects considerably the composition of food fats.
Keywords: pure cultures; conjugated linoleic acid; trans fatty acids; microwave heat treatment